2009
DOI: 10.1117/12.806130
|View full text |Cite
|
Sign up to set email alerts
|

A facial expression image database and norm for Asian population: a preliminary report

Abstract: We collected 6604 images of 30 models in eight types of facial expression: happiness, anger, sadness, disgust, fear, surprise, contempt and neutral. Among them, 406 most representative images from 12 models were rated by more than 200 human raters for perceived emotion category and intensity. Such large number of emotion categories, models and raters is sufficient for most serious expression recognition research both in psychology and in computer science. All the models and raters are of Asian background. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…A total of 336 face expressions of eight category are selected from TFEID ( Taiwanese facial Expression Image Database) [26] . Query images are selected at random from the test database.…”
Section: Results Analysismentioning
confidence: 99%
“…A total of 336 face expressions of eight category are selected from TFEID ( Taiwanese facial Expression Image Database) [26] . Query images are selected at random from the test database.…”
Section: Results Analysismentioning
confidence: 99%
“…To ensure and motivate our subjects in the performance of this task, actual monetary rewards were applied to mimic real-life events. Three types of facial expressions from the culture-based facial-expression database (Chen et al, 2009 , 2013 ) were selected to prime affective arousal in each group. Patterns on the PANAS and facial-expression ratings evidenced that facial primes were perceived by our subjects and successfully elicited corresponding affective arousal as planned, and this was further confirmed by the N170 and EEP results.…”
Section: Discussionmentioning
confidence: 99%
“…A split-plot design was adopted here. Subjects were randomly assigned into one of the three groups, and were exposed to one of the three types of facial expressions (i.e., happy, angry, and neutral faces) from the database (Chen et al, 2009 , 2013 ) prior to choosing the card in each trial. Subjects in the AN (and HN, respectively) group were randomly exposed to angry (and happy, respectively) faces (as the affective prime) in half of the trials and to neutral faces (as the neutral prime) in the other half of the trials (Figure 1D ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some may argue that such simplification may fail in certain parts of a face, such as the eyebrows and eye details that have a different coloration from the skin. However, we computed the size of these details for 76 faces from a database [26] and found that these features combined occupied only about 3% area of the face. Hence, for a face model with no highlights, the product of C and L in the interaction term in Eq 2 can be treated as negligible for our stimuli.…”
Section: Introductionmentioning
confidence: 99%